Strategi Perencanaan Sumber Daya Manusia Dalam Menghadapi Tantangan Era Digital - Oges Susfita Putri; Ella Afnira; Putri Febriyanti (Jurnal Pemimpin Bisnis Inovatif, 2024)
In the face of the digital era's rapid evolution, human resource planning has become increasingly crucial for organizations to maintain competitiveness and sustainability. This abstract explores strategic human resource planning (HRP) as a pivotal approach to navigating the complexities posed by digital transformation. The advent of digital technologies has revolutionized industries, requiring organizations to adapt swiftly to remain relevant and efficient. Strategic HRP involves aligning workforce capabilities and organizational goals with the demands and opportunities presented by digital advancements. Key considerations include forecasting future workforce needs, identifying critical skill gaps, and implementing robust talent acquisition and development strategies. Moreover, effective HRP entails leveraging data analytics and predictive modeling to anticipate HR requirements and optimize workforce planning initiatives.The challenges of the digital era necessitate proactive measures in talent management, such as upskilling current employees and recruiting digitally savvy talent. Organizations must foster a culture of continuous learning and adaptability to thrive in a digitally disrupted environment. Strategic HRP also encompasses developing agile HR policies and practices that can accommodate rapid technological changes and evolving employee expectations. Furthermore, integrating technologies like artificial intelligence and automation into HR processes can streamline operations and enhance decision-making capabilities.In conclusion, strategic human resource planning is indispensable for organizations seeking to harness the opportunities presented by the digital era while mitigating its inherent challenges. By prioritizing agility, foresight, and innovation in HR practices, organizations can build a resilient workforce capable of driving sustainable growth and competitive advantage in the digital age.